Pengaruh sistem poles eve diacera terhadap kekasaran permukaanZirconia generasi 3y-tzp setelah tahap occlusal adjustment - Ananda Fadillah, Tri; Handojo, James (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Zirconia is a biomaterial in dentistry. There are two types of zirconia restorations, zirconia veneered with feldspathic porcelain (ZVP) and monolithic zirconia (MZ). Monolithic zirconia restorations are increasingly being used due to their strength and fracture resistance as well as their good aesthetic capabilities. 3Y-TZP is indicated for framework material in porcelain-coated crowns and fixed dental prostheses in posterior and anterior regions. The occlusal adjustment stage of the restoration could possibly produce high surface roughness. Goals: To determine the effect of EVE Diacera polishing system on the surface roughness of 3Y-TZP generation zirconia after occlusal adjustment stage. Methodology: The type of research conducted was a laboratory experiment which took place at the Dental Material and Testing Center of Research and Education (DMT Core) Laboratory, Faculty of Dentistry, Trisakti University, Jakarta. This study used samples produced by FOCUS Dental Lab Jakarta. The samples are in the form of 3Y-TZP monolithic zirconia blocks that have passed the sintering, polishing, and glazing stages. This study used a total of 18 research samples divided into two groups. Data will be obtained from the average surface roughness results from the surface roughness tester which will be analyzed for normality test and homogeneity test (p>0.05) with the use of SPSS application. Results: The study showed that there is an effect of EVE Diacera polishing system on the surface roughness of 3Y-TZP generation zirconia restorations after the occlusal adjustment stage. Conclusion: EVE Diacera polishing system has an effect on the surface roughness of 3Y-TZP generation zirconia.